2009
DOI: 10.1111/j.1442-2042.2009.02391.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases from testicular germ cell tumors: A retrospective analysis

Abstract: Objectives: To review our series of testicular germ cell tumors with brain metastases and to establish an optimal treatment strategy for them. Methods: Twenty-seven cases of testicular germ cell tumors from three institutions were retrospectively reviewed. Results: Twenty-six were non-seminomatous tumors and only one was a seminoma. Based on the International Germ Cell Consensus Classification, two cases were classified as good prognosis, seven as intermediate prognosis and 18 as poor prognosis. Chemotherapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…For patients with brain metastasis at initial diagnosis, 2-year survival rates range from around 30 to 54% and median survival from 15 to 56 months in the different series [8,9,10,11,12]. In these series, most of the patients were treated with upfront chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with brain metastasis at initial diagnosis, 2-year survival rates range from around 30 to 54% and median survival from 15 to 56 months in the different series [8,9,10,11,12]. In these series, most of the patients were treated with upfront chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In most series, patients were treated with radiotherapy with or without chemotherapy [8,9,10,11,12]. …”
Section: Discussionmentioning
confidence: 99%
“…Die Metastasierung von Seminomen erfolgt in der Regel lymphatisch in die retroperitonealen Lymphknoten oder hämatogen vorwiegend in Lunge und Leber. Sehr selten können häma-togene Seminommetastasen fast ubiquitär auftreten, beispielsweise auch in der Prostata [3,4,5,6]. Bislang wurden in der Literatur nur 4 weitere Fälle von Seminommetastasen in der Prostata beschrieben (.…”
Section: Diskussionunclassified
“…Author Population Significant prognostic factors Sehouli et al [19] Ovarian cancer, n = 74 KPS, number of brain metastases, histological grade, platinum sensitivity (multivariate) Cohen et al [2] Ovarian cancer, n = 72 Aggressive local treatment Growdon et al [6] Gynaecological cancers, n = 30 Extracranial disease, histology, use of chemotherapy (multivariate) Fokas et al [4] Bladder cancer, n = 62 Extracranial metastases, RPA class Rades et al [15] Bladder cancer, n = 33 Multivariate analysis revealed no significant prognostic factors Tremont-Lukats et al [24] Prostate cancer, n = 103 Adenocarcinoma vs other histology Nonomura et al [12] Testicular germ cell tumours, n = 27 Single brain metastasis (multivariate) Salvati et al [18] Sarcoma, n = 35 KPS, complete en-bloc surgery Rades et al [13] Unknown primary, n = 101 KPS, extracranial metastases, RPA class Bartelt and Lutterbach [1] Unknown primary, n = 47 KPS, surgical resection status (multivariate) Ruda et al [16] Unknown primary, n = 33 Number of brain metastases (multivariate)…”
Section: Tab 3 Prognostic Factors In Patients With Rare or Unknown Pmentioning
confidence: 99%